Desain Low-Cost Sistem Monitoring Pengukuran Potensi Tenaga Matahari dan Tenaga Angin - Aries Jehan Tamamy; Zaenal Arifin; Amalia Amalia (Universitas Syiah Kuala, 2019)
Renewable energy implementation could become the alternative for electrical energy supply in a remote area with no network for electricity and also could be implemented in an urban area to reduce electricity consumption in daily usage. One of the problems to implement renewable energy is how to measure solar power potential and wind power potential to decide the qualification to apply the system in a particular area. This research used Arduino Uno as the main Controller that connected to a Voltage sensor, Current Sensor ACS712 30A dan light intensity sensor BH1750 to measure solar power potential and also anemometer to measure wind power potential. Software design was done using Arduino IDE program that successfully produced stable Low-Cost system that can operate well with all kind of solar panel with maximum Voltage of 34.7 V and current ± 30 A. The results from system testing shows that the system has accuracy for voltage sensor with value of 99.2%, current sensor with value of 95.3% and light intensity sensor with value of 99.8% and also has excellent precision with SDR value for every sensor are 0.034%, 4.58% and 0.026%.